Research on simulation of 5G indoor distribution system based on ray tracing propagation model - Xin TAO; Junqing WAN; Yifeng LI; Xisheng XU; Nanting QIAO; Bin XU (Dianxin kexue, 2022)
The construction of indoor distribution system has become an effective means to solve the problem of deep coverage.At present, 5G network construction is developing rapidly, indoor distribution system construction is exploding, and the network planning and design of indoor distribution system needs to be more refined.How to effectively evaluate the indoor signal coverage effect becomes one of the important tasks of current indoor distribution system planning and design.A building was taken as the research object, the coverage performance index was calculated by ray-tracing propagation model simulation, and the results were compared with the road test data of the existing network.After correcting the relevant model parameters, the simulation is consistent with the actual measurement, and the demonstration simulation provides a reference basis for network deployment.